Estimasi Stok dan Serapan Karbon Tegakan Pinus (Pinus merkusii) Kecamatan Tapango Kabupaten Polewali Mandar - Yunita, Yuyun; Irundu, Daud; Agusfartham Ramli, Muhammad (Program Studi Kehutanan Fakultas Pertanian dan Kehutanan Universitas Sulawesi Barat, 2024)
Global warming is caused by an increase in carbon dioxide (CO₂), and greenhouse gases (GHG) in the atmosphere. Pine forests have the role of absorbing carbon dioxide in the atmosphere and storing it in the form of biomass. The aim of this research is to determine the amount of carbon stored and the carbon uptake of pine stands in Tapango District, Polewali Mandar Regency. Data collection was carried out in the pine forest of Tapango District, Polewali Mandar Regency in 27 plots measuring 20 meters x 20 meters. The measurement of stored carbon in this research was carried out indirectly (non-destructive sumpling) using an existing formulation approach. The results of the research show that the highest biomass and carbon values ​​are found in plot 20, while the lowest values ​​are found in plot 2. The total biomass in the pine forest in Tapango District, Polewali Mandar Regency is 686.86 tons per ha, while the total carbon stored is 322. 82 tons per ha, total carbon uptake of 1,182.69 tons per ha.